DaiTongXiao improves gout nephropathy by inhibiting inflammatory response through the TLR4/MyD88/NF-κB pathway - Liu, Feifan; Bai, Yuanmei; Wan, Yan; Luo, Shifang; Zhang, Linao; Wu, Xue; Chen, Rong; Yin, Zili; Xie, Yuhuan; Guo, Peixin (Frontiers in Pharmacology, 2024)
Introduction: Gouty nephropathy (GN) arises from factors like excessive purine intake, metabolic disorders or abnormal synthesis, and uric acid hypersaturation in the blood, leading to urate crystal deposition in kidney tissue. DaiTongXiao (DTX) is a remedy used by the Dai people of China. It shows efficacy in lowering uric acid levels and exhibits anti-inflammatory and kidney-protective properties. Methods: A GN rat model was induced using adenine and potassium oxonate. Following DTX administration, various parameters were assessed in urine, serum, and kidney tissue. Western blot analysis evaluated TLR4/MyD88/NF-κB signaling proteins, while immunofluorescence examined NF-κB nuclear expression. Results: DTX treatment improved kidney morphology, increased body weight, and kidney index and enhanced urinary levels of blood urea nitrogen (Bun), 24-h urinary protein, uric acid (UA), and allantoin in GN rats, reducing UA, Bun, creatinine (Cre), cystatin C (CysC), serum amyloid A (SAA), α1-microglobulin (MG), and β2-MG in serum analysis. Renal tissue assessments showed decreased xanthine oxidase (XOD), hydroxyproline (Hyp), α-smooth muscle actin (α-SMA), and collage type Ⅳ (COL-Ⅳ). Kidney damage severity was notably reduced. DTX lowered serum inflammatory factors like interleukin (IL) −18, tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), transforming growth factor-β1 (TGF-β1), and IL-1β in the rat serum, reducing chemokine monocyte chemoattractant protein-1 (MCP-1) and adhesion factor vascular cell adhesion molecule-1(VCAM-1). Western blotting demonstrated the downregulation of TLR4/MyD88/NF-κB pathway proteins, and immunofluorescence revealed reduced NF-κB expression in renal tissue. Discussion: DTX exhibits significant anti-GN effects by modulating TLR4/MyD88/ NF-κB pathway protein expression, reducing inflammatory factor release, and inhibiting GN progression.